2016
DOI: 10.1590/1982-0194201600014
|View full text |Cite
|
Sign up to set email alerts
|

Síndrome de Burnout entre mestrandos e doutorandos em enfermagem

Abstract: Objective: To investigate the occurrence of burnout syndrome and to identify its predictors in master's and doctoral students of graduate nursing programs. Methods: A cross-sectional, descriptive, analytic study performed with 129 master's and doctoral students from three public universities. The research instruments were a semi-structured questionnaire to characterize the participants, and the Maslach Burnout InventoryTM -Student Survey. Data were analyzed using descriptive, inferential statistics and multipl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 26 publications
(31 reference statements)
1
12
0
5
Order By: Relevance
“…For the students who are attending the Master's degree, this represents the penultimate semester of the course, but for the Doctorate, that is less than half of the course. The predominance of women in the samples of postgraduates analyzed was also recorded by other authors [5,7,11,12] and this, according to Faro, [2] is associated with the increase in the number of women who finished their postgraduation in Brazil since 2004. "Women remain as a majority in the Brazilian postgraduation" was a headline at CAPES in March 2018 (http://www.capes.gov.br/sal a-de-imprensa/noticias/8787-mulheres-permane cem-como-maioria-na-pos-graduacao-brasileira).…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…For the students who are attending the Master's degree, this represents the penultimate semester of the course, but for the Doctorate, that is less than half of the course. The predominance of women in the samples of postgraduates analyzed was also recorded by other authors [5,7,11,12] and this, according to Faro, [2] is associated with the increase in the number of women who finished their postgraduation in Brazil since 2004. "Women remain as a majority in the Brazilian postgraduation" was a headline at CAPES in March 2018 (http://www.capes.gov.br/sal a-de-imprensa/noticias/8787-mulheres-permane cem-como-maioria-na-pos-graduacao-brasileira).…”
Section: Discussionsupporting
confidence: 65%
“…The Burnout syndrome, assessed by the Maslach Burnout Inventory TM-Student Survey (MBI-SS), was detected in Nursing Postgraduate students. [12] Galdino et al [12] identified that 69.8% of the students had high scores in emotional exhaustion, 27% had high depersonalization, 24.8% had low academic efficacy and 11.6% had an indicative for Burnout syndrome.…”
Section: Introductionmentioning
confidence: 99%
“…In both undergraduate and postgraduate courses, this has drawn attention from the academia, although the results are still being published in scientific meeting or smaller journals (Louzada & Silva Filho, 2005;Santos & Alves Júnior, 2007;Malagris et al, 2009;Escobar & Verdinelli, 2010;Andrade et al, 2013;Valadares, Macedo, Alcântara, & Mafra, 2014;Silva & Vieira, 2015;J. S. Ferreira et al, 2016;Galdino, Martins, Haddad, Robazzi, & Birolim, 2016;Moura, Charão-Brito, & Lopes, 2017). Because of this, the leaders of important social, educational, political and economic groups should be alerted to evaluate the members of their groups, in order to slow things down and facilitate assertive decisions, without degrading the relationships.…”
Section: Introductionmentioning
confidence: 99%
“…Por vivenciarem uma fase de transição, os estudantes de ensino médio estão sujeitos às novas experiências e, ao mesmo tempo, são compelidos a renunciar sua própria vida social em prol do acesso à instituição de ensino superior, assim, muitas vezes como efeito colateral emerge o estresse exaustivo -denominado como Síndrome de Burnout (SB) (Tuominen-Soini, & Salmela-Aro, 2014). Essa exaustão configura a primeira dimensão da síndrome, associando-se ao absenteísmo estudantil, fadiga, declínio das capacidades de memória e concentração (Galdino, Martins, Haddad, Robazzi, e Birolim, 2016). Surgem ainda outros sintomas, como nervosismo, sentimentos de desamparo, vazio, solidão e tristeza que, em longo prazo, tornam-se gatilhos para o desenvolvimento de outras patologias relacionadas ao humor deprimido e ansiedade (Ovchinnikov, Palchenkova, & Kalachev, 2015; Galván-Molina, Jiménez-Capdeville, Hernández-Mata, & Arellano-Cano, 2017).…”
Section: Introductionunclassified